Novel Techniques for Ex Vivo Expansion of Cord Blood: Clinical Trials - Mehta, Rohtesh S.; Rezvani, Katayoun; Olson, Amanda; Oran, Betul; Hosing, Chitra; Shah, Nina; Parmar, Simrit; Armitage, Sue; Shpall, Elizabeth J. (Frontiers in Medicine, 2015)
Cord blood (CB) provides an excellent alternative source of hematopoietic progenitor cells (HPC) for patients lacking human leukocyte antigen (HLA)-matched peripheral blood or bone marrow graft for transplantation. However, due to the limited cell dose in CB graft, it is associated with prolonged time to engraftment, risk of graft rejection, infections and treatment-related mortality. To increase the cell dose, a variety of ex vivo expansion techniques have been developed. Results of traditional methods of CB expansion using cytokines alone were disappointing. Expanding CB cells with mesenchymal progenitor cells led to sizeable increase in graft content and improved engraftment. Other methods used HPC-differentiation blockers, such as nicotinamide analogs, copper chelators, inducing constitutive Notch signaling, or an aryl hydrocarbon receptor antagonist (StemReginin1). Many of these methods lead to substantial expansions of total nucleated cells and CD34+ cells, and significantly improved time to neutrophil or platelet engraftment in patients transplanted with the expanded products compared to the recipients of unmanipulated CBT. These studies differ not only in the expansion method, but also with regards to the cytokines used, patient population, conditioning regimens and transplantation practices, to name a few. Some of these methods employed expansion of a portion of CB unit in the setting of single CBT, while others in the setting of double CBT. Here, we review various procedures used for CB expansion and highlight some of the key differences. Novel methods of improving engraftment that aim at improving bone marrow homing potential of CB cells are not reviewed.